A detailed assessment of the land cover development in a territory with dispersed settlement area (case study Hriňová – Snohy, Slovakia) - Katarína Švoňavová; Vladimír Falťan; Veronika Piscová; Vladimír Šagát; František Petrovič (Nature Conservation, 2024)
This study focuses on the development of the landscape during a period of significant social changes in Central Europe from the middle of the 20th century, and evaluates the impact of the selected natural factors on landscape dynamics in the Snohy dispersed settlement area (cadaster of Hriňová, Slovakia). During the periods of feudalism and the democratic Czechoslovak Republic after 1918, private ownership of land prevailed on the territory of Slovakia. After 1948, in the period of the socialist establishment, the municipality was one of the few localities without collectivisation. We focused on the state and changes to the landscape structure based on remote sensing data analysis (1949, 2003, and 2018), as well as field research and archive photographs inspection. The study area is a part of the proposed Special Area of Conservation SKUEV4026 Meadows of Poľana and is situated near the border between the transition and buffer zones of the Poľana Biosphere Reserve. The state of land cover and its changes have been evaluated using a CORINE Land Cover modification at the 5th level. Results showed that the influence of the slope on agricultural extensification, deforestation, and afforestation, was the most pronounced. Since 1949, more than half of the land cover has changed across the study area. The most extensive changes were recorded in the spatial structure and composition of forest communities.